Burden of malaria in the Comoros, 1990–2021: findings from the global burden of disease study 2021 - Sheng Zhou; Sheng Zhou; Jiarui Zhang; Chengcheng Li (Frontiers in Public Health)
BackgroundMalaria is a major public health issue in the Comoros. Analyzing the malaria burden will aid in designing prevention, control, and eradication strategies based on scientific evidence.MethodsWe retrieved data from the 2021 Global Burden of Disease (GBD) database to assess the malaria burden in the Comoros in 2021, stratified by sex and age. The indicators used to measure this burden included the absolute numbers and rates of incidence, prevalence, and mortality, as well as disability-adjusted life years (DALYs), years of life lost (YLLs), and years lived with disability (YLDs). Decomposition analysis was used to quantify the contributions of demographic aging, population growth, and epidemiological changes to the malaria burden from 1990 to 2021. Joinpoint regression analysis was employed to examine temporal trends in the malaria burden over this period.ResultsIn 2021, females, particularly those under 40, had a higher overall malaria burden than males, except for the age-standardized incidence rate (ASIR) and the age-standardized mortality rate (ASMR). Individuals under 30 years of age experienced approximately 52% of new malaria episodes, 68% of prevalent cases, and 62% of YLDs. Children under 5 and those aged 15 to 30 accounted for about 41% of malaria-related deaths, 54% of YLLs, and 53% of DALYs. Between 1990 and 2021, the malaria burden in the Comoros declined substantially, with age-standardized incidence (ASIR), prevalence (ASPR), mortality (ASMR), and DALY rates (ASDR) decreasing by over 85%. Decomposition analysis indicated that epidemiological changes played a pivotal role in reducing disease burden. Over the past 32 years, the average annual percentage change (AAPC) in the ASPR was statistically significant at −7.60% (t = −2.68, p < 0.05). Moreover, the annual percentage change (APC) in ASIR and ASPR showed the most significant decline from 2012 to 2015, with APCs of −70.47% (t = −3.01, p < 0.05) and − 66.55% (t = −14.94, p < 0.05), respectively.ConclusionThis study indicates that women under 40, school-aged children, and adults under 30 in the Comoros bear a higher malaria burden. Although current malaria control measures are effective, achieving a malaria-free status will require integrated strategies.